2020
DOI: 10.3390/app10144864
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Electrochemical Characterization of Nanoporous Alumina Structures: Pore Size, Porosity, and Structure Effect

Abstract: Three nanoporous alumina structures (NPASs) obtained by the two-step anodization method were optically and electrochemically characterized. Two of the structures were symmetric (NPAS-Sf and NPAS-Ph) and one was asymmetric (NPAS-And); pore size ranged from 10 nm to 100 nm and porosity was 12% in the case of the symmetrical NPAS and 23% and 30% for each surface of the asymmetric structure NPAS-And(A) and (B), respectively. Optical parameters of the studied samples (refraction index and extinction coefficient) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 58 publications
(86 reference statements)
1
12
0
Order By: Relevance
“…Average values of the refractive index determined for the three IL/NPAS for both optical regions (visible and nir) are indicated in Table 4 . As it can be observed, the values of the refractive index obtained for the IL/NPAS samples do not differ significantly from the tabulated values previously indicated in Table 1 (4% increase considering the visible region) and following the same sequential order; however, these values are significantly higher (~28%) than those determined for the NPAS support (<n visible > = 1.277 ± 0.03 and <n nir > = 0.82 ± 0.23 [ 39 ]), which can be taken as a confirmation of adequate surface coverage by the corresponding IL. In this context, it should be indicated that the tabulated values of the ILs refractive index are usually determined at a given wavelength (or discrete number of wavelengths) for the visible region, covering these results a wider range of wavelengths.…”
Section: Resultsmentioning
confidence: 41%
See 2 more Smart Citations
“…Average values of the refractive index determined for the three IL/NPAS for both optical regions (visible and nir) are indicated in Table 4 . As it can be observed, the values of the refractive index obtained for the IL/NPAS samples do not differ significantly from the tabulated values previously indicated in Table 1 (4% increase considering the visible region) and following the same sequential order; however, these values are significantly higher (~28%) than those determined for the NPAS support (<n visible > = 1.277 ± 0.03 and <n nir > = 0.82 ± 0.23 [ 39 ]), which can be taken as a confirmation of adequate surface coverage by the corresponding IL. In this context, it should be indicated that the tabulated values of the ILs refractive index are usually determined at a given wavelength (or discrete number of wavelengths) for the visible region, covering these results a wider range of wavelengths.…”
Section: Resultsmentioning
confidence: 41%
“…Information on optical parameters of the studied samples was obtained from spectroscopic ellipsometry (SE) and light transmission/reflection measurements, which are two non-destructive techniques used commonly for the characterization of layered and/or modified thin films [ 63 , 64 ]. Figure 4 shows the wavelength dependence of the refractive index (n) determined for the IL/NPAS samples, which were obtained from spectroscopic ellipsometry (SE) experimental parameters (angles Ψ and Δ) taking into account the ellipsometer software and the variation of tanΨ and cosΔ with wavelength for the three IL/NPAS is presented as Supplementary Information (Figure S4) ; for comparison, n values for the NPAS [ 39 ] are also indicated in Figure 4 . Average values of the refractive index determined for the three IL/NPAS for both optical regions (visible and nir) are indicated in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical techniques are of great interest in the characterization of materials due to their non-invasive and non-destructive character. In particular, spectroscopic ellipsometry has already demonstrated their suitability for characterization of nanoporous alumina membranes with different pore size, porosity or structure [ 43 ], but also for biosensors characterization [ 44 ], while light transmission spectra allows estimation of differences in both geometrical parameters (pore-size/porosity) and surface material of analyzed samples [ 8 , 12 ]. Moreover, a particular property of nanoporous alumina structures (NPASs) obtained by the two-step anodization method such as their potoluminescence (PL) character, which is associated to the ionized oxygen vacancies and the carboxylate from the electrolyte solution incorporated into the NPAS during the fabrication process has also been reported [ 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The device was miniaturized to adapt it to the size of mice and to manufacture in biocompatible materials. It consists of two main components, a subcutaneous reservoir and an apheresis module endowed with tailored NPMBs [ 33 , 34 ], which were encapsulated together in a capsule made by Neuroscience Innovative Technologies ( Figure 1 A, part A). For this study, NPMBs have a pore size of 9 ± 2 nm.…”
Section: Methodsmentioning
confidence: 99%